1989
DOI: 10.1128/aac.33.4.522
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of colds in human volunteers challenged with rhinovirus by a new synthetic drug (R61837)

Abstract: This report describes double-blind placebo-controlled trials of a new synthetic antirhinovirus drug, R61837, which showed it to be effective in suppressing colds in human volunteers challenged with rhinovirus type 9. In one trial, R61837 was given by intranasal spray six times a day, commencing 28 h before virus challenge; treatment continued for 4 days and one dose (total dose, 25 mg). This regimen suppressed symptoms until 48 h after medication ceased, at which time colds developed. In another trial, medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 8 publications
1
41
0
Order By: Relevance
“…The findings of the present study were predicted by results obtained in experimentally infected volunteers (9) and help to confirm the validity of the human challenge model with regard to the evaluation of antirhinoviral agents. Previous studies of pirodavir and its narrower-spectrum predecessor, R61,837, found that intranasal administration was protective against rhinovirus illness when it was begun prior to viral challenge with a susceptible serotype (1,9) and, in the case of R61,837, when administration was begun during the incubation period before symptom onset (5). In contrast, when pirodavir (six sprays per day) administration was begun at 1 day after viral challenge, when the subjects were symptomatic, reductions in the frequency of viral shedding but no clinical benefits were found (9).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study were predicted by results obtained in experimentally infected volunteers (9) and help to confirm the validity of the human challenge model with regard to the evaluation of antirhinoviral agents. Previous studies of pirodavir and its narrower-spectrum predecessor, R61,837, found that intranasal administration was protective against rhinovirus illness when it was begun prior to viral challenge with a susceptible serotype (1,9) and, in the case of R61,837, when administration was begun during the incubation period before symptom onset (5). In contrast, when pirodavir (six sprays per day) administration was begun at 1 day after viral challenge, when the subjects were symptomatic, reductions in the frequency of viral shedding but no clinical benefits were found (9).…”
Section: Discussionmentioning
confidence: 99%
“…The literature on the common cold contains many studies on prophylactic use of such agents as interferons [19][20][21][22][23][24][25][26] and synthetic drugs 8,27,28 in attempts to prevent colds or shorten their duration. Interferon, for example has demonstrated varying degrees of prophylactic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Interferon, for example has demonstrated varying degrees of prophylactic efficacy. [20][21][22]24,26 Success with such agents has proven to be elusive to date, 8,[19][20][21][22][23][24][25][26][27][28] as most treatments either have had limited efficacy or have had side-effects, such as nasal irritation, that are more severe than the symptoms of the cold. Very few agents have been found to have any effect once the symptoms have developed, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Several compounds of the WIN series have proved to be efficacious in various animal models of enteroviral disease (16,25). R 61837, the prototype compound of the pyridazinamine series, has shown clinical efficacy in humans (1). A pilot clinical trial of pirodavir under double-blind, placebo-controlled conditions indicated that the compound has a clinical effect in humans (13).…”
Section: Methodsmentioning
confidence: 99%